Eficiência de absorção e utilização de potãssio por plantas de soja em solução nutritiva - Sacramento, Luis Vitor Silva do [UNESP]; Rosolem, Ciro Antonio [UNESP] (FapUNIFESP (SciELO), 1998)
A greenhouse experiment was conducted in a factorial design of randomized complete blocks, with three replications, to study plantage response of soybean cultivars on efficiency: update (EAB); conversion (EC) and utilization, as well as utilization index (IU) by soybean cultivars. Four soybean cultivars (IAC 17, IAC 18, IAC 11 e FT 2) were grown in nutrient solutions with either adequate or deficient K levels (0.5 and 1.82 mmol. L-1) and harvested 20, 40 and 60 days after plant emergence (DAPE). The plants were separated in top, median and lower leaves, stems and roots, dried, ground and analyzed for K contents. Regardless of cultivar, in deficient plants K was translocated from the other organs to median leaves, in order to maintain its K contents. This behavior was particularly evident in 'IAC 11' and 'IAC 18'. Well nourished plants showed higher EAB than deficient plants. 'IAC 17' and 'IAC 18' showed higher EAB at either adequate or deficient K. levels. 'FT 2' showed highest EUK in deficient solutions at 40 DAPE (immediately before flowering), and the lowest EUK at 60 DAPE. The utilization index was helpful in determining cultivar plasticity to adapt to K deficiency. The highest plasticity was observed for 'FT 2' at 40 DAPE and for 'IAC 18' at 60 DAPE. K-deficient plants were more efficient in EC, yielding more dry matter for K uptake unit.
Efficiency of potassium uptake and utilization by soybean plants
Keywords: Glycine max (L.) Merrill; Potassium; Soybean; Soybean cultivars; Uptake; Utilization efficiency